How to present : the ultimate guide to presenting live and online - Bowden, Michelle (John Wiley & Sons, Inc., 2023)
Learn the secrets of successful speaking, communicating and presenting Do you get nervous when presenting at work? Do you want to showcase your knowledge, influence people and accelerate your career? How to Present reveals the winning formulas that ensure you are a confident, clear and influential presenter every time. Presentation skills expert Michelle Bowden shares her internationally proven system for exceptional presenting, starting with analysis (plan what you would like to achieve), then design (put your presentation together) and delivery (communicate your message for results). This second edition is fully updated with all new strategies for presenting in online and hybrid sessions. Presenting online can be effective and engaging--you just need to know what to do, and then do it! How to Present will help you: maximise your impact in meetings, conferences and conversations manage your nerves so you feel calm and confident engage your audience and master the art of persuasion structure your message cleverly and with deliver with authority command attention and achieve your goals Whether you're speaking to one person or thousands, live or online, this is the essential guide to becoming an outstanding presenter who is memorable for all the right reasons!